Socio-biological basis of the practical nutrition of rural schoolchildren in the South of Uzbekistan and its rational organization - Rakhmatullayev, Yorqin (E-Library Karshi EEI, 2020)
Socio-biological basis of the practical nutrition of rural schoolchildren in the South of Uzbekistan and its rational organization